Nilai Komunikasi Antarbudaya Di Kecamatan Mandah Kabupaten Indragirihilir Provinsi Riau - Siti Saputri; Tomi Hendra (Fakultas Ilmu Sosial dan Ilmu Politik, 2022)
Indonesia, which is famous for its multicultural society, requires a good intercultural communication system to avoid conflicts between people. The research method that the author uses is qualitative with a descriptive approach. Through the research phase, namely observation, interviews and documentation as well as using data analysis techniques. so that it can find out how the value of intercultural communication, supporting factors and inhibiting factors in implementing the value of intercultural communication in Khairiah Mandah Village, Mandah District, Indragiri Hilir Regency, Riau Province. The results of the research that the authors found showed that the value of intercultural communication in the Khairiah Mandah village went well after several policies from the local government such as conducting counseling and socialization, this was marked by the occurrence of a harmonious life between different religions and ethnicities. However, for coastal areas the form of intercultural communication values ​​does not run completely. There are still some forms of social inequality that are found, such as there are still boundaries in some areas. but it does not turn into a dispute because the Chinese understand the beliefs held by Islam.